h y Bogdan Ciubotaru, Gabriel-Miro Muntean. - Ciubotaru, Bogdan; Muntean, Gabriel-Miro.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The field of network programming is so large, and developing so rapidly, that it can appear almost overwhelming to those new to the discipline. Answering the need for an accessible overview of the field, this text/reference presents a manageable introduction to both the theoretical and practical aspects of computer networks and network programming. Clearly structured and easy to follow, the book describes cutting-edge developments in network architectures, communication protocols, and programming techniques and models, supported by code examples for hands-on practice with creating network-based applications. Topics and features: Presents detailed coverage of network architectures, including the latest wireless heterogeneous networks, communication protocols, and support for communication-based services Gently introduces the reader to the basic ideas underpinning computer networking, before gradually building up to more advanced concepts Provides numerous step-by-step descriptions of practical examples in tandem with the theoretical discussions Examines a range of network programming techniques, from server-side and client-side solutions to advanced client-server communication models Reviews network-based data storage and multimedia transfer Includes an extensive set of practical code examples, together with detailed comments and explanations This comprehensive and authoritative guide is an invaluable asset for all researchers interested in computer networking, whether they wish to understand the underlying architectures and paradigms, or to obtain useful advice on building communication-based programs. Advanced undergraduate and postgraduate students will also find the book to be an excellent supplementary textbook for modules on network programming.
Introduction -- Network Architectures -- Network Communications Protocols and Services -- Basic Network Programming -- Sockets -- Socket-Based Client Server Communication -- Support for Communication-Based Services -- Server-Side Network Programming -- Client-Side Network Programming -- Advanced Client-Server Network Programming -- Conclusion.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer Science; Computer Communication Networks; Programming Techniques; Special Purpose and Application-Based Systems